Preserving Spontaneous Ventilation in ASA III Patients: Transtracheal Block as a Primary Anesthetic Strategy for Complex Bronchoscopy - Yoga Indrawan Pratama; Ruddi Hartono; Muhammad Farlyzhar Yusuf (HM Publisher, 2026)
Introduction: Fiberoptic bronchoscopy (FOB) in patients with American Society of Anesthesiologists (ASA) physical status III presents a significant anesthetic challenge. General anesthesia carries risks of hemodynamic instability and respiratory compromise, while conventional topical anesthesia is often insufficient for cough suppression. This study evaluates the efficacy of transtracheal block (TTB) combined with dexmedetomidine as a primary anesthetic strategy to preserve spontaneous ventilation in high-risk patients. Case presentation: We present a serial case report of four adult males (aged 43-66 years) with severe pulmonary comorbidities, including advanced lung malignancies, atelectasis, and massive pleural effusion. All patients were classified as ASA III. The anesthetic protocol utilized a multimodal approach: intravenous dexmedetomidine sedation (loading dose 1 mcg/kg, maintenance 0.2-0.7 mcg/kg/hr) combined with a TTB using 20 mg of 2% lidocaine. All procedures were successfully completed without conversion to general anesthesia. Hemodynamic monitoring revealed that mean arterial pressure (MAP) and heart rate variability remained within 15% of baseline. No episodes of desaturation (SpO2 < 90%) or significant periprocedural respiratory distress were observed. Patients demonstrated rapid recovery with minimal coughing (Visual Analog Scale for Cough < 2/10) and were discharged from the ICU within 24 hours. Conclusion: Transtracheal block combined with dexmedetomidine provides profound airway anesthesia while maintaining spontaneous ventilation and hemodynamic stability. This technique represents a superior safety profile compared to general anesthesia for complex bronchoscopy in patients with compromised respiratory reserve.